2011
DOI: 10.1177/147323001103900226
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disc Changes after 1 h of Running: A Study on Athletes

Abstract: The lumbar spines of 25 long-distance runners were examined using an upright magnetic resonance imaging scanner. All volunteer runners were scanned before and after running for 1 h. Scanning was performed with the runners seated upright (neutral), leaning forwards (flexion) and leaning backwards (extension). All measured discs showed a reduction in disc height after 1 h of running. A significant reduction in disc height was observed in all three body positions (neutral, flexion and extension) after 1 h of runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
7
16
0
2
Order By: Relevance
“…The disc height reduction concurs with earlier results that have displayed a successive disc height reduction from repetitive loading in both experimental loading models and in clinical studies (Gooyers et al 2012; Dimitriadis et al 2011; Cheung et al 2003; Masuoka et al 2007). In general the loaded FSUs displayed smaller nucleus with less distinct boundaries compared to the controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The disc height reduction concurs with earlier results that have displayed a successive disc height reduction from repetitive loading in both experimental loading models and in clinical studies (Gooyers et al 2012; Dimitriadis et al 2011; Cheung et al 2003; Masuoka et al 2007). In general the loaded FSUs displayed smaller nucleus with less distinct boundaries compared to the controls.…”
Section: Discussionsupporting
confidence: 91%
“…Similar MRI findings as disc signal reduction can be seen clinically on MRI after a 1 h run (Dimitriadis et al 2011) and spinal injuries in the growth zone and epiphyseal plate are often seen among adolescent athletes (Baranto et al 2006; Hellstrom et al 1990; Sward et al 1990a; Sward et al 1990b; Granhed & Morelli 1988). The results support that recovery and hysteresis loop are important steps to avoid fatigue and failure injuries.…”
Section: Discussionmentioning
confidence: 60%
“…If they did not regularly measure their body mass, body fat may have 1 Intervertebral discs undergo a significant strain after 1 hr of running (Dimitriadis, et al, 2011). In contrast, side lying end-range lumbar flexion position results in a statistically significant mean spine height gain of 4.78 ± 4.01 mm while side lying mid-range lumbar flexion position results in a statistically significant mean spine height gain of 5.84 ± 4.4 mm (Gerke, Brismée, Sizer, Dedrick, & James, 2011).…”
Section: Kommentar [Si3]mentioning
confidence: 99%
“…Upright endurance activities, that is, jogging or running, have been considered beneficial for intervertebral disk health, 31 although running for only one hour may decrease disk height. 32,33 It has been suggested that frequent running may have detrimental longterm effects on lumbar intervertebral disks, which may be prevented by the more dynamic form of exercise and optimizing running frequency. 31,32 In a Japanese study, the prevalence of DD was lower among runners with at least 5 years of active participation than among controls who may have participated in competitive sport activities a maximum of three times a week.…”
Section: Discussionmentioning
confidence: 99%